PENGAPLIKASIAN SISTEM EVAPORATIVE KONDENSOR PADA AC SPLIT 2 PK - Andhika Ega Pratama; Zulina Kurniawati; RB Budi Kartika W (Politeknik Penerbangan Indonesia Curug, 2019)
Evaporative Cooler (EC) condenser is a process of air cooling that flows across wet surface and evaporate water from that wet surface so the environment air temperature become lower (air cooling). Application of EC on Air Conditioning (AC) Split will lower the environment air temperature that flow to condenser, so it will influence the work of AC Split. This experiment head to know increase in the work of AC Split that used EC and Mist Nozzle that produce fog. The result of the experiment shows that using EC, temperature of the environment air become lower compared to without using EC with the difference 4ºC in temperature, this causes the condenser pressure and evaporator pressure become lower, so the consumption of electrical energy will be lower and the work of AC Split increase to 20%.